Ketidakadilan Gender dalam Novel Midah Simanis Bergigi Emas Karya Pramoedya Ananta Toer Tinjauan Sastra Feminis Sebagai Bahan Ajar Di SMA N 1 Tawangsari - Widayanti, Titik, Prof. Dr. Ali Imron Al-Ma'ruf, M.Hum (2016)
This study aimed to describe (1) the background sosiohistoris Pramoedya Ananta Toer, (2) set out the structure that builds novel Midah Simanis Bergigi Emas, (3) describes the form of gender inequality in the novel Midah Simanis Bergigi Emas, and (4) implementation as a teaching material language and Indonesian literature at the high school. This study used descriptive qualitative method. The object of this research is gender inequality in the novel Midah Simanis Bergigi Emas by Pramoedya Ananta Toer. The data in this study of words, quotes, sentences, and aragraphs that contain gender inequalities present in the novel Midah Simanis Bergigi Emas. Sources of primary data in this study of novel Midah Simanis Bergigi Emas by Pramoedya Ananta Toer, 2015, publisher Lentera Dipantara. Secondary data sources in this study in the form of books, journals, articles that have relevance to this study. Data collection techniques used in this research is the engineering literature, see, and record. Mechanical validity of the data used in this study is a technique terianggulasi data. Data analysis technique used is the reading of the heuristic method, followed by reading hermeneutics. Based on the analysis performed, it can be summed up as follows: (1) Background sosiohistoris Pramoedya Ananta Toer that he was born in Blora February 6, 1925 , his works such as novels , short stories, and a biography , (2) based on the structure of the building novel Midah Simanis Bergigi Emas was discovered theme , and the fact the story containing the groove , haracterizations , and background , (3) gender inequalities are found in the form of (a) stereotyping or labeling negative against women , (b) the burden of domestic work and longer ( burden ) , (c) the subordination of men in which there are forms of subordination in the world labor and households , (d) the marginalization in which includes discrimination in the household and discriminates against the world of work , and (e) of violence or violence in the form of physical, sexual , and prostitution , (4) the results of this study can be implemented on language learning and Indonesia in high school literature class XI for the second semester according to three criteria , namely language teaching materials , psychology and cultural background . Keywords: teaching materials in high school, feminism, gender inequality, Midah Simanis Bergigi Emas.